Effects of perceived English teacher support on student engagement among Chinese EFL undergraduates: L2 motivational self system as the mediator - Zhang, Wenxing; Hu, Jiayue (Frontiers in Psychology, 2025)
IntroductionStudent engagement is a vital evaluation index in the learning process of English learners and serves as a key indicator of the effectiveness and quality of college English teaching.MethodsBased on the perspective of the second language motivational self system theory, this study used a structural equation model to explore the general profile of 2,633 Chinese undergraduates of English as a foreign language (EFL) perceived teacher support, second language (L2) motivation, and student engagement in English classrooms, and the interrelationships among the three variables.ResultsThe results showed that teacher support and student engagement were at high levels, and L2 motivation was at a medium-high level in English learning. Perceived teacher support significantly correlated with L2 motivation, and their profound influence on student engagement. The indirect effect results showed that the L2 motivational self system mediated the effect of perceived teacher support on student engagement, and L2 learning experience exerted a greater mediating effect compared to the ideal L2 self and ought-to L2 self.DiscussionThese findings deepen the understanding of the interaction mechanism between these variables and provide helpful references to improve student engagement and learning effectiveness.